The Effect Of Warm Water Foot Hydrotherapy With A Mixture Of Kaempferia Galanga Rhizom On Blood Pressure In Elderly Hypertension : Pengaruh Foot Hydrotherapy Air Hangat Dengan Campuran Rimpang Kencur (Kaempferia Galanga) Terhadap Tekanan Darah Pada Lansia Dengan Hipertensi - widiyono, widiyono (Infomasi dan Promosi Kesehatan, 2025)
Introduction: The prevalence of hypertension by age group shows that the elderly suffer the most, at over 62% compared to other age groups. Untreated hypertension can increase morbidity and reduce quality of life. Hypertension can be treated with non-pharmacological therapy in the form of foot hydrotherapy with herbal plants, such as galangal. The purpose of this study was to determine the effect of warm water foot hydrotherapy with galangal rhizome on blood pressure. Methods: The research method used was a pre-experimental with a pre-post test without a control group design. Purposive sampling was used to determine the study sample, with 31 elderly respondents. The implementation of foot soak therapy using warm water with galangal rhizome at a dose of 6 grams, four times in six days for two weeks, with a duration of 15 minutes per session. Blood pressure was measured using a calibrated sphygmomanometer and stethoscope. Data analysis was carried out using the Wilcoxon test. Results: The Wilcoxon test results for systolic and diastolic blood pressure (p=0.001), meaning a p value <0.05, statistically showed a difference in blood pressure before and after the intervention. Based on these analysis results, it can be concluded that soaking feet in warm water mixed with galangal has an effect on reducing blood pressure in the elderly. Conclusion : Soaking feet in warm water mixed with galangal is effective in lowering blood pressure in elderly people with hypertension. Nurses should provide this intervention. However, conventional treatment should be continued. This therapy is only complementary. Keywords : Foot Hydrotherapy, Galangal, Blood Pressure, Elderly